A Study of Water Flux through Forward Osmosis Membrane Using BrineWater System - A. Al-Hemiri, Adel; M. Kamil, Marwah (Iraqi Journal of Chemical and Petroleum Engineering, 2013)
The present work aims to improve the flux of forward osmosis with the use of Thin Film Composite membrane by reducing the effect of polarization on draw solution (brine solution) side.This study was conducted in two parts. The first is under the effect of polarization in which the flux and the water permeability coefficient (A) were calculated. In the second part of the study the experiments were repeated using a circulating pump at various speeds to make turbulence and reduce the effect of polarization on the brine solution side. A model capable of predicting water permeability coefficient has been derived, and this is given by the following equations: Z=Z0 +C.R.T/9.8(d2/D2+1) [Exp. [-9.8(d2/D2+1) A.M/p .t]-1]